Long-term acrylamide exposure exacerbates brain and lung pathology in a mouse malaria model. (May 2021) - Ngo-Thanh, Ha; Thuy, Trang Dam; Suzue, Kazutomo; Kamitani, Wataru; Yokoo, Hideaki; Isoda, Koji; Shimokawa, Chikako; Hisaeda, Hajime; Imai, Takashi
Abstract: The consumption of dietary acrylamide (ACR), a carcinogen, results in the dysfunction of various organs and the immune system. However, the impact of ACR exposure on the progression of infectious diseases is unknown. This study investigated the effect of ACR on the progression of malaria infection using a mouse model of malaria. C57BL/6 mice were continuously treated with ACR at a dose of 20 mg/kg bodyweight/day for six weeks (long-term exposure) or phosphate-buffered saline (PBS). Next, the mice were infected with the rodent malaria parasite, Plasmodium berghei NK65 (PbNK). Parasitemia and survival rate were analyzed in the different treatment groups. Magnetic resonance imaging (MRI) and histopathological analyses were performed to evaluate the effect of ACR exposure on the morphology of various organs. Long-term ACR exposure exacerbated PbNK-induced multiorgan dysfunction. MRI and histopathological analysis revealed signs of encephalomeningitis and acute respiratory distress syndrome in the PbNK-infected long-term ACR exposure mice, which decreased the survival rate of mice, but not in the PbNK-infected long-term PBS exposure group. These findings enhance our understanding of the impact of ACR on the progression of infectious diseases, such as malaria. Graphical abstract: Image 1 Highlights: Long-term ACR exposure caused earlier death in mice with malaria. Long-term ACR exposure induced brain damage in mice with malaria. Signs of meningitis appeared in long-term ACR-exposed mice with malaria. Long-term ACR exposure exacerbates malaria-associated acute respiratory distress syndrome.